Removal of Partially Impacted Mandibular Third Molars with and without Flap: A Comparison of Two Surgical Techniques - Ahmed, Naseer; Khan, Muhammad Nazir; Mahmood, Saad; Adeel, Muhammad Ramzan; Yasir, Ammar; Saeed, Shahrukh Ahmed (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To compare with and without flap removal of partially impacted mandibular third molars in terms of mean pain and mean swelling on the second post-operative day. Study Design: Quasi-experimental study. Place and duration of Study: Department of Oral and Maxillofacial Surgery, Armed Forces Institute of Dentistry, Rawalpindi Pakistan, from May to Nov 2021. Methodology: Sixty cases (30 in each Group) with partially impacted mandibular third molar with mesioangular impaction aged 18-45 years were included. Random allocation of patients was done to the removal with flap (Group-A) and without flap (Group-B). On the second post-operative day, the outcome of pain and swelling in patients was measured based on the Visual Analogue Scale (VAS between 0 to 10 cm points for pain and swelling on a scale of 0 to 3). Results: The mean pain score was 5.67±1.30 in Group-A (with flap) versus 2.97±1.25 in Group-B (without flap) (p-value,<0.001). The mean swelling score was 5.40±1.16 for Group-A (with flap) versus 2.97±1.15 for Group-B (without flap) (p-value,<0.001). Conclusion: The surgical extraction of the partially impacted mesioangular mandibular third molar without buccal flap reflection and bone ostectomy resulted in less post-operative pain and swelling than surgery with buccal flap reflection and bone ostectomy.